Experiences of Pharmacy Trainees from an Interprofessional Immersion Training - Daubney Boland; Traci White; Eve Adams (MDPI AG, 2018)
Interprofessional education is essential in that it helps healthcare disciplines better utilize each other and provide team-based collaboration that improves patient care. Many pharmacy training programs struggle to implement interprofessional education. This purpose of the study was to examine the effect of a 30-h interprofessional training that included pharmacy students to determine if the training helped these students build valuable knowledge and skills while working alongside other health care professions. The interprofessional training included graduate-level trainees from pharmacy, behavioral health, nursing, and family medicine programs where the trainees worked within teams to build interprofessional education competencies based on the Interprofessional Education Collaborative core competencies. Sixteen pharmacy trainees participated in the training and completed pre- and post-test measures. Data were collected over a two-year period with participants completing the Team Skills Scale and the Interprofessional Attitudes Scale. Paired sample t-tests indicated that, after this training, pharmacy trainees showed significant increases in feeling better able to work in healthcare teams and valuing interprofessional practice.